# How do I solve this problem?

##
Solve the equation by first using a sum to product formula:

#sin4theta-sin2theta=cos3theta#

Solve the equation by first using a sum to product formula:

##### 1 Answer

#### Answer:

I got

#### Explanation:

Let's start by rewriting:

#sin(2theta + 2theta) - sin(2theta) = cos(2theta + theta)#

#sin(2theta)cos(2theta) + sin(2theta)cos(2theta) - sin(2theta) = cos(2theta)costheta - sin(2theta)sintheta#

#2sin(2theta)cos(2theta) - sin(2theta) = cos(2theta)costheta - sin(2theta)sintheta#

#sin(2theta)(2cos2theta - 1) = cos(2theta)costheta - 2sinthetacosthetasintheta#

#sin2theta(2cos2theta - 1) = costheta(cos2theta - 2sin^2theta)#

Now recall that

#((2sinthetacostheta)(2cos2theta - 1))/costheta = 1 - 4sin^2theta#

#2sintheta(2(1 - 2sin^2theta) - 1) = 1 - 4sin^2theta#

#2sintheta(2 - 4sin^2theta - 1) = 1 - 4sin^2theta#

#4sintheta - 8sin^3theta - 2sintheta = 1 -4sin^2theta#

#0= 8sin^3theta - 4sin^2theta - 2sintheta + 1#

Now let

#0 = 8y^3 - 4y^2 - 2y + 1#

#0 = 4y^2(2y - 1) -(2y - 1)#

#0 = (4y^2 - 1)(2y - 1)#

#y^2 = 1/4 or y = 1/2#

#y= +-1/2#

#sintheta = +-1/2#

#theta = pi/6 + pi/2n#

However, we must account for when we cancelled the cosine above. This can be a dangerous game, because you can lose solutions. However, if you recognize it, you can prevent that from happening.

Since the equation at this point is a product, the equation will hold true whenever

Thus,

Hopefully this helps!